Single parameter of inverse proportion between mortality and age could determine all mortality indicators in the first year of life - Dolejs, Josef (Journal of theoretical biology, 2016)
Mortality increase with age in adult population has been studied and modeled by many authors, but relatively little attention has been given to mortality decrease with age after birth. Data split in more detailed age categories can newly test mortality decrease with age. Age trajectories of mortality are studied in 20 age categories in the specific age interval 1-365 days. Four basic models mentioned in literature are tested here. The linear model and the linear model with the specific slope -1 in the log-log scale represent the most successful formalism. Mortality indicators describing the first year could be determined by a single parameter of the model with slope -1 in the log-log scale. All conclusions are based on published data which are presented as a supplement.
Keywords: dospělí; Female; Models; teoretické modely; Infant; dítě; předškolní dítě; Mortality; novorozenec; Age Factors; Adult; Linear Models; mladý dospělý; ženské pohlaví; Infant mortality; Aging; Adolescent; věkové faktory; lidé; Infant, Newborn; Age; Aged, 80 and over; mortalita; lineární modely; Algorithms; Male; kojenec; Aged; Child, Preschool; Young Adult; stárnutí; algoritmy; lidé středního věku; Child; senioři nad 80 let; senioři; mužské pohlaví; Models, Theoretical; Middle Aged; mladiství; Mortality indicators; Humans